O exercicio fisico induz ajustes termorregulatorios ecardiovasculares que são mediados pela neurotransmissãocolinérgica dos núcleos ventromediais hipotalâmicos - Samuel Penna Wanner (2006)
The aim of this study was to evaluate the participation of cholinergic muscarinic receptors inthe ventromedial hypothalamic nuclei (VMH) on heat balance, cardiovascular adjustments andcentral fatigue during treadmill exercise (24 m.min-1, 5% inclination). Rats were submittedto two experimental situations separated by an interval of at least two days. Tail skintemperature, core body temperature (Tb) and arterial pressure were measured after theinjection of 200 L of 2,5 x 10-2 M methylatropine (Atr) or 0.15 M NaCl solution (Sal)into the VMH. Atr injection into the VMH amplified the exercise-induced increase in Tb andresulted in a delay in the rise of skin temperature. The increased heat storage needed totrigger the heat loss mechanisms observed in VMH Atr-treated rats may be responsible forthe 37% decrease in the performance of these animals (21.0 ± 2.9 min Atr vs. 33.5 ± 3.4 minSal; n = 8; p 0.001). Cholinergic blockade of VMH has also acelerated the blood pressureadjustments (mean arterial pressure maximal value: 132.6 ± 3.9 mmHg at 3 min Atr vs.125.2±4.1 mmHg at 9 min Sal; n = 7), which were related to the percentage of total exercisetime. We conclude that cholinergic muscarinic receptors in the VMH modulate sympatheticactivation and facilitate heat loss during exercise. Furthermore, these adjustments inducedby intra-ventromedial cholinergic neurotransmission determine exercise time until fatigue.